Curiosity Journalism, or the First Decades of Newsgames. (June 2020) - Bogost, Ian
As a veteran developer of newsgames and a coauthor of the book Newsgames: Journalism at Play, I revisit the origins, past promise, and current reality of the form. Like many other interventions in games outside entertainment, newsgames have great promise, but that promise has not yet been realized. Rather than ignoring these lessons, the next generation of scholars, researchers, critics, journalists, and developers should learn the difficult lessons from the past and incorporate them into their future efforts.